“Analysis of patients of poisoning in a tertiary care teaching hospital in Assam: A retrospective study” - Madan Chandra Das; Rupsmita Buzarbaruah; Bhaskar Jyoti Dutta; Senjam Renuka Singh; Swopna Phukan; Diptimayee Devi; Subhajit Mitra (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Acute poisoning is a national health reverence linked to legal issue across the globe. Distinct geographical places have distinct toxic substances as per socio-economic standard associated with psycho-social status, as well as variable wholesomeness and death rates. Aim: To evaluate the mode and pattern of poisoning treated in a tertiary level medical hospital in north east India. Methods: Following ethical approval, data of 591 acutepoisoning case records gathered within 24 months were sourced from the medical record department and analyzed. Except ethanol intoxication and snake bite cases, all cases of poisoning were included. Results: Female group accounted corrosive poisoning at a higher (64.97%) rate ( = 48.979, df = 19, p-value=.000). Greatest number (63.28%) accounted in the age group of 15-30 (ANOVA, p=0.000<0.05). Month of September had a higher rate (13.62%). Pesticideand sedatives accounted for the majority in young female (45.34%). Familial disharmony and marital discord were most leading factors followed by depression ( =272.220, p =0.000). Approximately 578 individuals were reverted; 13 passed away. Poisoning with organophosphate (OP) proved highly fatal. Discussion: Poisoning is a medico-legal emergency. Public awareness regarding fatality of toxic substances and prompt care of poisoning is crucial. Strict proven protocol on uses of toxic chemicals might reduce the mortality.